2021
DOI: 10.1108/jfmm-03-2020-0050
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fashion blogger credibility, engagement and homophily on intentions to buy and e-WOM. Results of a binational study

Abstract: PurposeThe study aims to contribute to the knowledge on the role of the fashion bloggers in the product adoption process in both advanced and emerging markets. Specifically, the study investigates the impact of credibility, engagement and homophily on intentions to buy fashion products recommended by the blogger.Design/methodology/approachThe empirical research builds on an online survey with a sample of 402 consumers (189 Italian and 213 Taiwanese). The proposed model was tested through structural equation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 87 publications
0
23
0
3
Order By: Relevance
“…Therefore, the marketing literature (Pansari and Kumar, 2017;Halaszovich and Nel, 2017;Chu and Kim, 2011;Kumar et al, 2010) acknowledges that engagement exerts a significant and positive impact on e-WOM. Following this line of enquiry, studies in the context of blogging have confirmed this relationship (Mainolfi and Vergura, 2021;Muniz and Shau, 2005). In fact, empirical evidence shows that readers who experiment a positive engagement toward a blog are more likely to spread a positive word-of-mouth about the blogger.…”
Section: The Influence Of Blog Engagement On Intention To Taste and Visit And On E-wommentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, the marketing literature (Pansari and Kumar, 2017;Halaszovich and Nel, 2017;Chu and Kim, 2011;Kumar et al, 2010) acknowledges that engagement exerts a significant and positive impact on e-WOM. Following this line of enquiry, studies in the context of blogging have confirmed this relationship (Mainolfi and Vergura, 2021;Muniz and Shau, 2005). In fact, empirical evidence shows that readers who experiment a positive engagement toward a blog are more likely to spread a positive word-of-mouth about the blogger.…”
Section: The Influence Of Blog Engagement On Intention To Taste and Visit And On E-wommentioning
confidence: 88%
“…Therefore, it is possible to speculate that if there is a high level of engagement, it is likely that users will continue to use the blog and follow the blogger's suggestions. Past studies (Mainolfi and Vergura, 2021;Jim enez-Castillo and S anchez-Fern andez, 2019) testified that the interaction and participation in blog conversations can stimulate the readers' willingness to purchase the products suggested by the blogger. Similarly, with regard to the tourism industry, several studies have found that travel blogs may influence travel decisions through the degree of engagement (Huang et al, 2010).…”
Section: The Influence Of Blog Engagement On Intention To Taste and Visit And On E-wommentioning
confidence: 99%
“…Additionally, another study confirmed that WOM can be used to supplement tourism marketing efforts by influencing residents' attitudes toward the tourist destination ( Segota et al, 2021). It should be noted that WOM relies on the sharing of information (Amani, 2022a;Bastos and Moore, 2021;Mainolfi and Vergura, 2022). Similar to this, the buyer-supplier relationship entails the act of exchanging necessary information between suppliers and buyers (Mushi et al, 2021;Ried et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the term "purchase intention" refers to a person's intentional purpose to make an attempt to purchase a certain brand of product. The process of consumers making purchase choices is a dynamic one, and purchase motivations are an integral element of this process (Mainolfi and Vergura, 2021). The term "purchase intention" refers to the state of mind of a customer in which they have the purpose to acquire a certain item or service (Wu et al, 2012).…”
Section: 2mentioning
confidence: 99%
“…The term "purchase intention" refers to the state of mind of a customer in which they have the purpose to acquire a certain item or service (Wu et al, 2012). The purchase intention can also be defined as the conscious plan that an individual puts forth regarding making an effort in order to buy a particular brand (Spears and Singh, 2004;Mainolfi and Vergura, 2021). According to this definition, the purchase intention is dependent on the conscious of the person; therefore, the purchase intention represents a personal behavioral tendency (Tsai and Men, 2017).…”
Section: 2mentioning
confidence: 99%